PENGARUH PENGATURAN SKEMA FEEDING DAN KONSENTRASI LIMBAH HEXAVALENT CHROMIUM (Cr(VI)) PADA STABILITAS PROSES ANAEROB : STUDI KASUS LIMBAH CAIR LABORATORIUM JURUSAN TEKNIK KIMIA UNIVERSITAS GADJAH MADA (JTK UGM) - , GREGORIUS PRIMA INDRA BUDIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to improve the performance of the laboratoryâs wastewater treatment facility in Chemical Engineering Department of Gadjah Mada University, which contains chromate. The research is emphasized on formulating the composition of starter and substrate feeding frequency to maintain the performance stability of anaerobic process in wastewater treatment plant on Chemical Engineering Department Gadjah Mada University.Disturbance to the process was assumed to be mainly caused by the chromateâs effect. Measurements were conducted in each digester with respect to: (i) the effect of addition of cow manure, conducted by comparing between the digester without cow manure (containing starch 20 g/L